(untitled) (Geo-Eco-Marina, 2024)
The month of August 2023 brought sad news to the Romanian geological community, the passing of the research geologist Dr. Emil Avram, a member of the Geology-Geography Institute of the Romanian Academy and the Geological Institute of Romania, for 35 years. He was devoted for a long period of time mainly on paleontological studies, starting with the bachelor‘s thesis on fossil traces from Vrancea, presented in 1961 at the University of Bucharest. Following that year, as a co-author, he published the first paleontological monograph on vertebrate traces from the Miocene of the Romanian Subcarpathians, which became a classic and indispensable work for paleoichnological research all over the world.